Availability of phosphorus for maize in crop-livestock integration system - Galetto, Shivelly; Fonseca, Adriel; Harkatin, Silvano; Auler, André; de Carvalho, Igor (Revista Ciência Agronômica, 2014)
The objectives of this study were to assess the concentrations of available phosphorus (P) extracted using the Mehlich-1 (M1), ion exchange resin (IER) and modified Morgan (MM) methods after 36 months of experimentation with the application of phosphates in a crop-livestock integration system (CLIS). Moreover, this study aimed to assess which extraction method provides the best correlation of P concentrations with the maize crop attributes. The treatments consisted of applying annual doses of P2O5 on the soil surface of the total area during the sowing of winter forage crops in the form of triple superphosphate (TSP), rock phosphate (RP) or magnesium thermophosphate (MTP). After 36 months of experimentation, soil samples were collected from the 0-5, 5-10, 10-15 and 15-20 cm layers to assess the concentrations of available P. The dry matter yield (DMY), the grain yield (GY), the accumulation of phosphorus in the dry matter (P-DM) and the export of phosphorus (P-Ex) were quantified in maize. The IER method extracted greater amounts of available P, followed by the M1 and MM extractions. The treatments that included the application of TSP and either the M1 or IER extractions had similar efficacies when correlated with the DMY, GY, P-DM and P-Ex attributes of maize. The P extracted by the IER was most correlated with P-DM and P-Ex for the water-insoluble P sources (RP and MTP). The MM solution was ineffective at predicting the availability of P for maize grown in a soil with that had received varying doses and sources of P applications in a CLIS.